From the Cradle to the Grave of an Infection: Host‐Pathogen Interaction Visualized by Intravital Microscopy. Issue 5 (27th November 2019) - Handschuh, Juliane; Amore, Jonas; Müller, Andreas J.
Abstract: During infections, interactions between host immune cells and the pathogen occur in distinct anatomical locations and along defined time scales. This can best be assessed in the physiological context of an infection in the living tissue. Consequently, intravital imaging has enabled us to dissect the critical phases and events throughout an infection in real time in living tissues. Specifically, advances in visualizing specific cell types and individual pathogens permitted tracking the early events of tissue invasion of the pathogen, cellular interactions involved in the induction of the immune response as well the events implicated in clearance of the infection. In this respect, two vantage points have evolved since the initial employment of this technique in the field of infection biology. On the one hand, strategies acquired by the pathogen to establish within the host and circumvent or evade the immune defenses have been elucidated. On the other hand, analyzing infections from the immune system's perspective has led to insights into the dynamic cellular interactions that are involved in the initial recognition of the pathogen, immune induction as well as effector function delivery and immunopathology. Furthermore, an increasing interest in probing functional parameters in vivo has emerged, such as the analysis of pathogen reactivity to stress conditions imposed by the host organism in order to mediate clearance upon pathogen encounter. Here, we give an overview on recent intravital microscopy findings of host‐pathogen interactions along the course of an infection, from both the immune system's and pathogen's perspectives. We also discuss recent developments and future perspectives in extracting intravital information beyond the localization of pathogens and their interaction with immune cells. Such reporter systems on the pathogen's physiological state and immune cell functions may prove useful in dissecting the functional dynamics of host‐pathogen interactions. © 2019 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of International Society for Advancement of Cytometry.